IMPLEMENTASI EDUKASI TERHADAP SELF EFFICACY PADA LANSIA YANG MENGALAMI NYERI RHEUMATOID ARTRITHIS (RA) DI UPT PELAYANAAN SOSIAL LANJUT USIA - Nikmah, Villa Edilla Alfiatun; Pratama, Muchti Yuda; Olivia, Nina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The pain sensation in Rheumatoid Arthritis (RA) leads to decreased self-efficacy, namely an individual's belief in their ability to perform activities. One of the non- pharmacological methods to address this pain problem is through education on warm compress therapy. This therapy provides a warming sensation that can enhance comfort and reduce pain. The objective of this study is to describe the implementation of warm compress education on self-efficacy in elderly patients with RA. This research employed a descriptive design with a nursing care approach, encompassing the stages of assessment, diagnosis, intervention, implementation, and evaluation. The study involved two elderly respondents experiencing moderate pain intensity and self-efficacy scores below 30 in RA. Warm compress therapy was administered for 20 minutes, twice a week. To assess self-efficacy, the Patient Self-Efficacy Questionnaire (PSEQ) was used. The findings indicated an increase in self-efficacy from below 30 to above 60, as well as improvement in respondents' ability to perform daily activities. In addition, joint pain intensity decreased from a moderate level to a mild level. This study is expected to serve as a reference for patients to implement the therapy and as a source for developing Standard Operating Procedures (SOP) for pain management in RA patients at elderly care facilities.